2022
DOI: 10.3389/fevo.2022.1020703
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the spatial-temporal patterns of conflicts between humans and Asiatic black bears (Ursus thibetanus) around the Gaoligongshan Nature Reserve, China

Abstract: Conflicts between humans and Asiatic black bears (Ursus thibetanus) are widespread in Asia and pose challenges to human-bear coexistence. Identifying effective mitigation measures requires a thorough understanding of human-bear conflicts (HBC). We assessed spatial-temporal patterns of HBC and their impact factors around the Baoshan Section of the Gaoligongshan Nature Reserve (GNNR) between 2012 and 2020. The results suggested that crop raiding by bears occurred most commonly, followed by beehive loss, livestoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 75 publications
1
4
0
Order By: Relevance
“…The human-bear interface can also significantly influence Additionally, the diminishing proximity between human settlements and the human-bear interface has intensified the potential for human-bear interactions. This trend aligns with previous studies (Harris et al, 2023) and 2020 (Ji, Wei, Liu, Li, Li, Huang, et al, 2022). Our interview surveys have indicated that most respondents perceive a discernible rise in human-bear interactions over the past two decades.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…The human-bear interface can also significantly influence Additionally, the diminishing proximity between human settlements and the human-bear interface has intensified the potential for human-bear interactions. This trend aligns with previous studies (Harris et al, 2023) and 2020 (Ji, Wei, Liu, Li, Li, Huang, et al, 2022). Our interview surveys have indicated that most respondents perceive a discernible rise in human-bear interactions over the past two decades.…”
Section: Discussionsupporting
confidence: 90%
“…Bear poaching activities in the Mt. Gaoligong area have significantly decreased from 2000 to 2020 (Ji, Zhang, et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations